KOMPAKTIBILITAS KOMPOSIT ISOTROPIK Al/Al2O3 DENGAN VARIABEL WAKTU TAHAN SINTER - Widyastuti, Widyastuti; Siradj, Eddy S; Priadi, Dedi; Zulfia, Anne (UI Scholars Hub, 2008)
Compactibility of Al/Al2O3 Isotropic Composite with Variation of Holding Time Sintering. The requirement of component with structural ability, light weight and also strength is increasing base on Metal Matrix Composites (MMCs) by aluminum as matrix (AMCs). A structural ability is connected to composites compactibility which is depend on quality of interfacial bounding. Powder metallurgy is one of method to produce composite with powder mixing, compacting and sintering. Volume fractions reinforced and sintering time can influence composites compactibility. Volume fractions reinforced variable can produce different reinforcement effect. Beside that, on sintering enables the formation of new phase during sintering time. In this research, Al/Al2O3 isotropic composites are made with aluminum as matrix and alumina (Al2O3) as reinforced. Volume fraction reinforced used 10%. 20%. 30% and 40%. Sintering temperature and compaction pressure are each 600o C and 15 kN. The tests that applied are compression and metallographic test. The result that obtained is optimum compactibility of Al/Al2O3 composite reached at holding time 2 hour. During sintering, new phase can occur that is aluminum oxides (alumina), with unstable properties. The best volume fraction reinforced and holding time sintering are 40% and 2 hours.